A Radiographic Evaluation of Missing of Permanent First Molars in a Group of Iranian Children and Adults: A Retrospective Study - Mostafa Rezaie; Jannan Ghapanchi; Abdolaziz Haghnegahdar; Leila Khojastehpour; Hooman Khorshidi; Heshmatollah Heidari (International Journal of Dentistry)
The missing of permanent first molars influences the occlusal status and dental health. The purpose of this study was to determine the prevalence of missing first molar teeth in a selected population of Shiraz, Iran. Methods. A total of 2206 panoramic views of patients aged from 7 to 75 years old were inspected for missing of permanent first molars. Patients were categorized into five age groups: from 7 to 15, 16 to 30, 31 to 45, 46 to 60, and more than 60 years old. Data were categorized according to sex, age, and number of lost teeth using SPSS software. Results. No first molar was missing in 59.9% of the cases, 17.05% had lost one, 10.4% had lost two, 7.2% had lost three, and 5% were missing all four of their permanent first molars. The mandibular first molar was the most commonly lost tooth, and the left side in both jaws was more affected than the right side. There was a positive relation between age and missing first molar. Conclusions. A missing first molar is a common finding in southern Iran population. Due to the important role of permanent first molars in occlusion, more education and dental care is recommended to preserve these teeth.